Matrilineal communities, patriarchal realities : a feminist Nirvana uncovered - Ruwanpura, Kanchana N. (Zubban, 2006)
In rejecting falsely homogenizing accounts of women’s lives, feminist economists have, in recent years, unlocked the multiple ways in which gendered relations of dominance and subordination are maintained. One of the key differences they have turned their attention to is ethnicity. This study of Muslim, Sinhala and Tamil households in Sri Lanka examines both the commonality of patriarchal structures and economic problems in such households, as well as the differences created by the ethnicities that divide them. The author looks at the nature and reliability of kinship support for female heads and the reciprocal obligations in terms of female propriety and conventional conduct extracted from female heads. She questions development policies premised on the patriarchal household and argues for a recognition of diversity and complexity.